2023
DOI: 10.1186/s12864-023-09843-y
|View full text |Cite
|
Sign up to set email alerts
|

Full-length transcriptome characterization and comparative analysis of Gleditsia sinensis

Feng Xiao,
Yang Zhao,
Xiurong Wang
et al.

Abstract: As an economically important tree, Gleditsia sinensis Lam. is widely planted. A lack of background genetic information on G. sinensis hinders molecular breeding. Based on PacBio single-molecule real-time (SMRT) sequencing and analysis of G. sinensis, a total of 95,183 non-redundant transcript sequences were obtained, of which 93,668 contained complete open reading frames (ORFs), 2,858 were long non-coding RNAs (LncRNAs) and 18,855 alternative splicing (AS) events were identified. Genes orthologous to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…G. velutina is endemic to Hunan Province, China, and is a rare and endangered plant under national key protection 41 . Stress-related genes had been positively selected during the evolution through comparative transcriptome analysis of Gleditsia genus 42 . In this study, positive selection was acting on five genes ( rpoA , rpl20 , atpB , ndhA , ycf4 ), which were identified under positive selection (Ka/Ks > 1), Ka/Ks ratio of most gene were less than 1, pairwise Ka/Ks analysis showed that most of the chloroplast genes of Gleditsia species underwent purifying selection, the purifying selection on most chloroplast genes within Gleditsia would be evolutionary result of the preservation of the adaptive characteristics of Gleditsia species.…”
Section: Discussionmentioning
confidence: 99%
“…G. velutina is endemic to Hunan Province, China, and is a rare and endangered plant under national key protection 41 . Stress-related genes had been positively selected during the evolution through comparative transcriptome analysis of Gleditsia genus 42 . In this study, positive selection was acting on five genes ( rpoA , rpl20 , atpB , ndhA , ycf4 ), which were identified under positive selection (Ka/Ks > 1), Ka/Ks ratio of most gene were less than 1, pairwise Ka/Ks analysis showed that most of the chloroplast genes of Gleditsia species underwent purifying selection, the purifying selection on most chloroplast genes within Gleditsia would be evolutionary result of the preservation of the adaptive characteristics of Gleditsia species.…”
Section: Discussionmentioning
confidence: 99%